1999
DOI: 10.1212/wnl.53.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reorganization of motor cortex outputs after arm amputation

Abstract: Reorganization of the motor system can be present more than 20 years after amputation. Furthermore, differential patterns of reorganized corticospinal output were found for different stump muscles, which might be due to varying amounts of ipsilateral corticospinal projections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 21 publications
3
57
0
Order By: Relevance
“…While the brains of subjects with amputation are nondisabled, significant reorganization occurs after the injury. After amputation, the human brain undergoes reorganization of the motor cortex in the areas previously designated to the missing limb [25][26][27]. It has been shown that areas previously delegated to the missing limb begin functioning with adjacent areas of the cortical map.…”
Section: Discussionmentioning
confidence: 99%
“…While the brains of subjects with amputation are nondisabled, significant reorganization occurs after the injury. After amputation, the human brain undergoes reorganization of the motor cortex in the areas previously designated to the missing limb [25][26][27]. It has been shown that areas previously delegated to the missing limb begin functioning with adjacent areas of the cortical map.…”
Section: Discussionmentioning
confidence: 99%
“…TMS studies of M1 reorganization following peripheral injury have clearly established that the stimulation intensities required to evoke MEP responses are strongly affected by amputation-induced deafferentation (4,9). MEP latency reduction has also been described for stump muscles in amputees, correlating inversely with the extent of a given muscle's representation in M1 (4,19).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from human and animal models show that, when deprived of its afferent sensory input and/or its motor effectors, the primary sensory (S1) and motor (M1) cortical regions undergo plastic modifications (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that limb amputation or deafferentation induces changes in primary sensory (S1) and motor (M1) cortices (reviewed by Chen et al, 2002), with evidence deriving from electroencephalography (Flor et al, 2000;Grüsser et al, 2001;Karl et al, 2001), transcranial magnetic stimulation (TMS) (Cohen et al, 1991;Pascual-Leone et al, 1996;Röricht et al, 1999;Mercier et al, 2006), magnetoencephalography (Flor et al, 1995), and functional magnetic resonance imaging (fMRI) (Lotze et al, 1999;Giraux et al, 2001;Grü sser et al, 2004). A remapping of cortical topography in upper limb amputees is consistently found, with enlargement and increased activation of the S1/M1 face area after stump stimulation (Ramachandran et al, 1992;Karl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%